Civil Legal Consequences of Asset Use Crypto as a Pawn Guarantee - Siregar, Dahris (Fakultas Hukum Universitas Widya Mataram, 2026)
As specified in the Civil Code's Article 503, crypto assets as intangible commodities can be categorized as intangible objects. In addition, since crypto assets have economic value and can be traded, they can be used as collateral. Documents known as